PENERAPAN METODE SIMULASI DALAM MENINGKATKAN KETERAMPILAN MENULIS TEKS EKSPLANASI - Isnani Arianti; Fadly Akbar (Universitas Negeri Makassar, 2023)
Improving Explanatory Text Writing Skills Using the Simulation Method. This study aims to describe the explanation writing skills of Class VII students of SMPN I Tonra by applying the explanation method. This research is class action research. This research was conducted in Class VII of SMP I Tonra, Bone Regency, for the 2021/2022 academic year. This Classroom action research was carried out by applying two cycles of data collection using observation and testing techniques. The results showed that students' skills in writing explanatory text increased from cycle 1 to cycle 2.